THE NECESSITY ANALYSIS OF MAJALENGKA WISDOM–BASED TEACHING MATERIALS TO ENHANCE STUDENTS’ CRITICAL THINKING SKILLS - Irma Sofiasyari; Luqman Rohmad Maghribi (Universitas Majalengka, 2025)
Critical thinking represents a core skill that students must master to face the challenges of the Industrial Revolution 4.0 era. Teachers foster this skill by developing teaching materials rooted in local wisdom. Learning resources that combine visual elements with cultural values create more meaningful learning experiences. This study investigated the need for Majalengka-based teaching materials to enhance students’ critical thinking. Using a descriptive qualitative method, the researchers conducted interviews and observations with eight teachers and fifth- and sixth-grade students from two elementary schools. The results show an urgent need to design teaching materials grounded in Majalengka local wisdom, since current resources remain generic and do not explicitly target critical thinking or cultural identity. Students require varied and innovative materials that can motivate learning while embedding local values. Incorporating Majalengka wisdom into instructional content strengthens both critical thinking and cultural identity. Future researchers should develop illustrated storytelling materials based on Majalengka local wisdom to advance critical thinking among elementary students.